Lobar Torsion Following Bilateral Lung Transplantation. Issue 2 (3rd December 2014) - Stephens, Georgina; Bhagwat, Krishna; Pick, Adrian; McGiffin, David
ABSTRACT Torsion of lobes of the lung is a rare complication following lung transplantation. We present a case of counterclockwise torsion of the right lung allograft and review of nine additional cases in the literature of lobar torsion following lung transplantation. A high degree of suspicion is needed for early diagnosis with rapid surgical intervention to preserve lung viability. doi: 10.1111/jocs.12476 (J Card Surg 2015;30:209–214)